Systemic Risk: Amplification Effects, Externalities, and Policy Responses - Anton Korinek (Oesterreichische Nationalbank (OeNB), 2009)
The worst financial crises since the Great Depression has forced central bankers and policymakers across Europe and around the globe to take unprecedented policy measures to deal with systemic risk, i.e. the risk that the financial system ceases to perform its function of allocating capital to the most productive use because of financial difficulties among a significant number of financial institutions. This paper develops a parsimonious model of systemic risk in the form of amplification effects whereby adverse developments in financial markets and in the real economy mutually reinforce each other and lead to a feedback cycle of falling asset prices, deteriorating balance sheets and tightening financing conditions. The paper shows that the free market equilibrium in such an environment is generically inefficient because constrained market participants do not internalize that their actions entail amplification effects. Therefore they undervalue the social benefits of liquidity during crises and take on too much systemic risk. We use our framework to shed light on a number of current policy issues. We show that banks face socially insufficient incentives to raise more capital during systemic crises, that bailouts which are anticipated can be ineffective, and that expectational errors are considerably more costly during crises than in normal times. Furthermore we develop an analytical framework for macro-prudential capital adequacy requirements that take into account systemic risk. We also analyze a new channel of financial contagion and explain why private agents will take insufficient precautions against contagion from other sectors in the economy.
Keywords: E31; E32; E24; J51; 330; financial crises; amplification effects; liquidity; systemic risk; systemic externalities; social pricing kernel; macroprudential regulation